Economic Viability of Vehicle-to-Vehicle Energy Trading in EV Charging Ecosystems - Somefun, Tobiloba Emmanuel; Oni, Oluwafemi Emmanuel; Longe, Omowunmi Mary (International Journal of Energy Economics and Policy, 2025)
This study investigates the economic feasibility of Vehicle-to-Vehicle (V2V) energy trading from the perspective of electric vehicle (EV) owners acting as energy providers. A milestone has been achieved due to advancements in technology in bidirectional charging systems. However, the profitability of peer-to-peer energy transfers remains underexplored. In this study, a return on investment (ROI) framework is developed in MATLAB/Simulink, which incorporates battery degradation costs, variable energy pricing (flat and time-of-use), and controlled discharge profiles. Simulation results using a 48 V, 100 Ah lithium-ion battery reveal that ROI is most sensitive to V2V sale price and battery cost, while charging tariff exerts limited influence. Break-even analysis shows that ROI becomes positive when sales price exceeds R3.60/kWh or battery cost drops below R14,000. Furthermore, three-dimensional sensitivity surfaces confirm that the economic viability of V2V energy exchange is primarily constrained by capital cost and revenue dynamics. These findings provide actionable insights for designing market-driven V2V frameworks and guiding policy interventions aimed at promoting distributed energy sharing.